Glycan engineering of the SARS-CoV-2 receptor-binding domain elicits cross-neutralizing antibodies for SARS-related viruses - Shinnakasu, Ryo; Sakakibara, Shuhei; Yamamoto, Hiromi; Wang, Po-hung; Moriyama, Saya; Sax, Nicolas; Ono, Chikako; Yamanaka, Atsushi; Adachi, Yu; Onodera, Taishi; Sato, Takashi; Shinkai, Masaharu; et al. (The Journal of experimental medicine, 2021)
Broadly protective vaccines against SARS-related coronaviruses that may cause future outbreaks are urgently needed. The SARS-CoV-2 spike receptor-binding domain (RBD) comprises two regions, the core-RBD and the receptor-binding motif (RBM); the former is structurally conserved between SARS-CoV-2 and SARS-CoV. Here, in order to elicit humoral responses to the more conserved core-RBD, we introduced N-linked glycans onto RBM surfaces of the SARS-CoV-2 RBD and used them as immunogens in a mouse model. We found that glycan addition elicited higher proportions of the core-RBD–specific germinal center (GC) B cells and antibody responses, thereby manifesting significant neutralizing activity for SARS-CoV, SARS-CoV-2, and the bat WIV1-CoV. These results have implications for the design of SARS-like virus vaccines.